Offering energy efficiency under imperfect competition and consumer inattention - Christian Tode (Institute of Energy Economics at the University of Cologne (EWI), 2016)
Energy efficiency is considered to be a win-win situation for both the economy and the environment. Producing products and services at lower energy input and related input costs can contribute to climate change abatement and economic competitiveness. Actual implementation of energy efficiency falls short to expectations, though. For one thing, research suggests that consumer inattention is an underlying force for underinvestments. For another thing, energy supply markets are often characterized by imperfect competition. Do firms in the energy retail market have incentives to voluntarily introduce energy efficiency? Or should informational regulation inform inattentive consumers? In this article I show that consumer inattention and imperfect competition are the crucial drivers for firms' decisions to introduce or conceil energy efficiency to customers. I find two symmetric equilibria: One in which both firms introduce energy efficiency and one in which both firms conceil energy efficiency. Equilibrium coordination depends on the distribution of consumers that are attentive to energy efficiency and consumers that are not. Further, mandatory disclosure laws are found to be weakly welfare increasing.
Keywords: D83; L13; L41; 330; Imperfect Competition; Consumer Inattention; Product Differentiation; Disclosure; Energy Efficiency